INFORMATION AND COMMUNICATIONS TECHNOLOGIES IN FUNCTION OF TEACHING PROCESS - Denić, Nebojša; Gavrilović, Snežana; Kontrec, Nataša (Bulletin of Natural Sciences Research, 2017)
This paper, based on the extensive research of relevant professional literature, will present and elaborate possible aspects of influence which information-communications technologies (ICT) have on educational process. Contemporary information-communications technologies and their use in teaching process resulted in numerous enhancements of teaching process altering traditional methods of learning and teaching. With the aim of confirming theoretical postulates researches were conducted on candidates with specific educational degrees in various forms of traditional teaching and teaching with educational software. The survey was conducted on a control and experimental group, on a sample of 1542 candidates. The candidates were observed in a period of approximately five months. The results of this research indicate that the candidates taught by use of educational software have shown far greater level of achieved knowledge and significantly higher motivation for learning. The participants of the experimental group actively participated in the acquisition of their competences. The contribution of this paper is in the new methodological approach to the organization of education, which significantly improves the teaching process, its goals and outcomes.
Keywords: Education; teaching; educational software